Pengaruh Pemberian Arang Sekam Padi Dan Pupuk P Terhadap Pertumbuhan Dan Produksi Tanaman Jagung Manis (Zea mays saccharata Sturt) Di Lahan Gambut - Yudi Firmansyah; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to look at the effect of husk charcoal and interaction of husk charcoal paddy and P fertilizer are good for increasing the yield of sweet corn on peatlands. The research was carried out on peat land, Jl. Manunggal, Tuah Madani Village, Tampan District, Pekanbaru. This research was conducted for 4 months starting from September to December 2017. The study was carried out experimentally using factorial randomized block design (RBD). the first factor is a combination of husk charcoal mixture A1 = husk charcoal 2.5 ton.ha-1, A2 = husk charcoal 5 ton.ha-1, A3 = husk charcoal 7.5 ton.ha-1. The second factor is TSP fertilizer dosage, P0 = TSP fertilizer 50 kg.ha.-1, P1 = TSP fertilizer 100 kg.ha.-1, P2 = TSP fertilizer 150 kg.ha-1. The parameters observed were leaf area, plant growth rate, harvest  is day, weight of cob per 6 m2, weight per cob with screw, weight per cob without screw, cob length and cob diameter. The data obtained were analyzed statistically with variance and continued with a DNMRT further test at the level of 5%. The results showed that the interaction of rice husk charcoal and P fertilizer significantly affected the plant growth rate, leaf area, weight per cob per 6 m2, weight per cob with screw, weight per cob without screw, cob length and cob diameter. The dose of rice husk charcoal 7.5 ton.ha-1 and fertilizer P 150 kg.ha.-1 give higher corn crop production which is 9,173 kg per 6 m2 / 15.25 ton.ha-1.Keywords: sweet corn, husk charcoal, P fertilizer , Peatlands.